The MPACT OF RESEARCH AND DEVELOPMENT (R&D) PROGRAMMES ON COMMUNITY PHARMACY PRACTISE - Ramandeep Kaur, Devinder Kumar (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
An vital role for community pharmacy R&D in Australia's developing practise of community pharmacy is being played. Community pharmacy has implemented a limited number of Cognitive Pharmacy Services (CPS) produced via R&D, showing a sluggish shift in practise. R&D plays a critical role in community pharmacy practise change, however little is known about the operation and its effectiveness in facilitating such transformation. The R&D programme was viewed as having a significant impact on the development of CPS. The R&D initiatives, they said, have a significant impact on policy, finance and the application of CPS into reality. In the community pharmacy sector, successful Knowledge Translation (KT) is impacted by a variety of context- and facilitation-related variables. These factors have a role in policy choices and their subsequent implementation.